An Analysis of Internationally Diversified Portfolios Based On World Equity Markets Data from 2001-2011 - Guan, Fang (2012)
This paper takes data from equity markets from 42 countries in order to build an internationally diversified portfolio. The method is similar to traditional domestic diversification. The objective is to build a minimum variance portfolio, and the results suggest that the diversified position should be much more preferred compared to the simple domestic market. This paper also carries out the study on the impact on the portfolio performance with the change of weight in the domestic market. The results prove that moving from a complete domestic portfolio into a more international portfolio can largely improve the performance.